PENINGKATAN LITERASI ANAK MELALUI PENERAPAN STRATEGI PARENTING ‘MONTESSORI’ PADA ANAK BERUSIA 3-5 TAHUN: SASTRA ANAK - Rahmah, Muftihatur; Nensilianti, Nensilianti; Tuflih, Muhammad Alfian (Fakultas Bahasa dan Sastra Indoensia, 2024)
This research explores the application of Montessori parenting strategies to enhance literacy in children aged 3-5 years using Glenn Doman's approach. It focuses on implementing these strategies and the resulting improvements in children's literacy through fairy tales as a medium. Utilizing descriptive qualitative methods, data were collected via observation, interviews, notes, and documentation. The findings demonstrate an increase in literacy following the implementation of Montessori strategies. The fairy tale